Virginia Woolf’s To The Lighthouse: Lily Briscoe’s Archetypal Behaviour - Aslam, Humaira (The Journal of Humanities & Social Sciences, 2023)
The archetype is a psychosomatic concept that links body, psyche, instinct and image. Jung asserts that images evoke the aim of the instincts, implying that they deserve equal significance. Archetypes are recognized in outer behaviours, namely those that cluster around basic and universal experiences of life, like motherhood, birth, death and separation. They are also part of the human psyche and are observable to inner or psychic life such as anima, shadow, persona and so forth. Archetypal patterns are realized in the personality and are capable of infinite variations depending upon individual expression. To give archetypal expression to something is to interact consciously with the collective unconscious; i.e., to interact with the historic image in such a way as to give opportunities to the play of intrinsic opposing forces. In order to prevent psychic disproportions conscious and unconscious states are harmonious in a balanced person. Dissolution of the compromise between the conscious and the unconscious renders the opposition even more intense and results in psychic disequilibrium. When this tension becomes intolerable, a solution must be discovered and the only viable relief is a reconciliation of the two at a different and more satisfactory level. Thus, Lily Briscoe sees a harmony in Mrs. Ramsay that she would like to achieve but remains unable to until she realizes and overcomes the shortcomings in her personality. She achieves that harmony in her painting only when she imbibes the spirit of Mrs. Ramsay, after much thought over her strict feministic stance.